Revisiting IPPTN's roles and functions. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2006)
Earlier in the year the National Higher Education Research Institute (IPPTN) organized a workshop to determine its vision for the next five years, i.e., 2006 until 2010.